VD_FINDINFO HC / 2016 / 169 vom 5. Februar 2016 - VD Tribunal cantonal (2016)
ABUS DE DROIT, LOYER INITIAL, FORMULE OFFICIELLE, BAIL À LOYER, TRANSACTION EXTRAJUDICIAIRE | 2 al. 2 CC, 3 al. 2 CC, 270 al. 2 CO, 19 OBLF